WALI HAKIM ALASAN PANDEMI PERSPEKTIF KESADARAN HUKUM: (Studi KUA Cluring dan Tegadlimo) - Qorrie Cornea Sunarto; Isroqunnajah Isroqunnajah; M. Aunul Hakim (LP2M Universitas Ibrahimy, 2023)
The early 2020 pandemic restricted activities and marriage is one of the events that had an effect. The government has created on Large Scale Restrictions Enforcement to the Community Activities Restrictions Enforcement. So that some lineage guardians who lived in various regions were unable to attend the marriage contract. As a result, the Office of Religious Affairs initiated steps to assign custody to a magistrate guardian, which should still be possible for Taukil guardians to carry out without removing the lineage guardian. This research aims to analyze the use of magistrate guardians from the perspective of legal awareness theory. Things like this are field research that employs a qualitative descriptive approach. The collection of data used is interviews and documentation. The stage of data processing includes re-examination(editing), categorization (Clasifiying), analysis (analyzing), and conclusions (concluding). The result of this analysis revealed that the process to utilize the magistrate guardian was demonstrated by the presence of a letter of application for the magistrate guardian, then the Office of Religious Affairs would re-examine (Rafak) would re-examine (Rafak) the completeness of the files to unearth evidence relevant to the utilization of the magistrate guardian. In the circumstance of employing a magistrate guardian as the guardian of a marriage ceremony during a pandemic emergency to prevent slander and adultery, the Islamic Law perspective is a relief. Due to low levels of education, law enforcement factors, and inadequate facilities, lineage guardians legal cognizance regarding magistrate and Taukil guardians is very limited.